A sociologia paulista nas revistas especializadas (1940-1965) - Jackson, Luiz Carlos (Tempo Social, 2004)
The article analyzes the development of the social sciences in São Paulo in its formative beginnings (1940-1965), from the standpoint of its principal journals at that time. From this perspective, tensions and disputes more characteristic in that specific context among academic institutions, groups and actors are outlined within the different strategies adopted by those mentioned agents operating through the specialized journals in science and culture.